“My boat I do not leave”: right of land use in the Serra do Pardo National Park by the beiradeiros, Pará, Brasil (Research, Society and Development, 2018)
This paper analyses which territorial rights have the beiradeiros from Saint Sebastian village, located today in the Serra do Pardo National Park (SPNP), between São Felix do Xingu and Altamira (Pará). Field research have been effected, through targeted conversations with the beiradeiros, in order to understand their territorialization process and verify if they can been seeing as traditional people. Bibliographical research has also been effected, specially about the art. 42 of Law nr. 9.985/2000 validity, in order to verify the possibility of the sustainable use of the environment and of the natural resources of the areas used by them, instead of their resettlement. It was concludes that those beiradeiros are Amazon traditional population and that they can use rationally the natural resources from the SPNP, what doctrine and jurisprudence named double affection of the conservation units.